Left ileal conduit: A case report. Issue 2 (11th December 2019) - Nakamura, Kazuyoshi; Matsui, Kenichiro; Wakai, Ken; Sazuka, Tomokazu; Imamura, Yusuke; Sakamoto, Shinichi; Sekita, Nobuyuki; Ichikawa, Tomohiko
Abstract : Introduction: When ileal conduit construction is performed for urinary tract drainage during radical cystectomy, the conduit is usually constructed in the right lower abdomen. However, no reports have described ileal conduit construction in the left lower abdomen when it cannot be performed on the right side. In addition, some ingenuity is necessary for construction on the left. Case presentation: A 75‐year‐old woman visited our hospital with chief complaint of gross hematuria. Computed tomography and cystoscopy showed a huge bladder tumor, and blood analysis showed anemia. The patient was treated by radical cystectomy with ileal conduit construction. An ileal conduit was constructed in the left lower abdomen; it was impossible to construct in the right lower abdomen because of the abdominal wall scar hernia due to the past open surgery. Conclusion: We herein reported a patient who underwent ileal conduit for urinary diversion on the left side of low abdominal wall.